Students’ Perception of the Teacher Characters in EFL Face To Face Classroom Interaction - Rifdhah, Nadhifah; Abduh, Amirullah; Sakkir, Geminastiti (Journal of Excellence in English Language Education, 2024)
This research aims at 1) finding out how students perceive teacher character in face-to-face EFL class interactions. 2) finding out the impact of teacher character on students in face-to-face EFL classroom interactions. This research uses qualitative descriptive methods to know students' opinions about the teacher's character and the impact felt by students. The participants in this research were class XII MIPA at SMA Negeri 17 Makassar. In this study, the instrument was an interview. Interviews were conducted face to face. The samples were chosen using the snowball sampling technique. The first student was selected by one of the English teachers at the school and the next student will be selected directly by the first student. The findings showed that 1) three themes can categorize English teachers' characters: interaction characters, personal characters, and teaching characters. The findings also revealed that students prefer an English teacher who can be a motivator during interaction, that the teaching style can build students' sense of enthusiasm and ambitiousness, and that students can emulate. 2) students feel the impact of the English teacher's character, which has both positive and negative sides. From the research results, it can be concluded that the character of an English teacher varies depending on the personality of the teacher. Apart from that, the teacher's character can also have an influence on students where they can also asses and build students' enthusiasm for learning.